(untitled) (Bangladesh Medical Journal, 2014)
Disease pattern in a given population is generally determined by different ecological factors. Thus the objective of this cross-sectional study was to determine the pattern of skin diseases in a selected rural community of Dhamrai Upazila under Dhaka district. Out of 2645 patients attending a medical camp showed 410(15.5%) patients with dermatological problems. Among all, 260(63.4%) patients were males and 150(36.6%) were females with a male to female ratio of 1.7:1. Of these patients, 178(43.4%) had cutaneous infections and 234(56.6%) had non-infectious dermatoses. Few patients (2.7%) had more than one dermatoses. Fungal infection was the commonest infection seen (22.9%) and eczemas took an upper hand in non-infectious group (32.2%). Improvement in the standard of living, health education, improvement in the environmental sanitation and good nutritious food may help the people to bring down the skin disease in the rural part of country. DOI: http://dx.doi.org/10.3329/bmj.v41i1.18784 Bangladesh Medical Journal 2012 Vol. 41 No. 1; 50-52